Meningioma with Intra- and Peritumoral Abscess - Sannareddy, Rajesh Reddy; Lath, Rahul; Padua, Michelle de; Ranjan, Alok (Indian Journal of Neurosurgery, 2018)
The association of meningioma with intra- and peritumoral brain abscess is rare. All cases reported in literature had some focus of infection in the body. We report a 56-year-old man with well-controlled diabetes mellitus found to have a space-occupying lesion upon evaluation for headache, vomiting, and clumsiness of right upper limb. Perioperatively, pus was found intra- and perilesionally around a thick, capsulated, dural-based, vascular lesion. Histopathology was suggestive of meningioma, and Escherichia coli was isolated upon culture.
Keywords: brain tumor; meningioma; abscess